Addressing the complex etiology of Alzheimer''s disease: the role of p25/Cdk5. (July 2011) - Mungenast, Alison E; Tsai, Li-Huei
Alzheimer''s disease (AD) is an age-related neurodegenerative disorder characterized by the progressive loss of forebrain neurons and the deterioration of learning and memory. Therapies for AD have primarily focused upon either the inhibition of amyloid synthesis or its deposition in the brain, but clinical testing to date has not yet found an effective amelioration of cognitive symptoms. Synaptic loss closely correlates with the degree of dementia in AD patients. However, mouse AD models that target the amyloid-ββ pathway generally do not exhibit a profound loss of synapses, despite extensive synaptic dysfunction. The increased generation of p25, an activator of the cyclin-dependent kinase 5 (Cdk5) has been found in both human patients and mouse models of neurodegeneration. The current work reviews our knowledge, to date, on the role of p25/Cdk5 in Alzheimer''s disease, with a focus upon the interaction of amyloid-ββ and p25/Cdk5 in synaptic dysfunction and neuronal loss.